2020
DOI: 10.1177/1129729820950998
|View full text |Cite
|
Sign up to set email alerts
|

Prolonging the flush-lock interval of totally implantable venous access ports in patients with cancer: A systematic review and meta-analysis

Abstract: Background: Recently, some studies have shown that prolonging flush interval is safe and feasible for patients who complete chemotherapy. However, there is no consensus about the optimal flush interval for those patients. Objective: The purpose of this review was to evaluate whether the flush interval could be prolonged based on monthly interval for regular maintenance and to explore the optimal flush interval. Data sources: We searched the following databases for articles published between 1 January 1982 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Based on the current literature review and clinical experience, we consider it appropriate to extend the flushing and locking interval of ports to 8 weeks and more weeks. This conclusion is consistent with the recently published papers by Wu et al 31 and Bertoglio 32…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on the current literature review and clinical experience, we consider it appropriate to extend the flushing and locking interval of ports to 8 weeks and more weeks. This conclusion is consistent with the recently published papers by Wu et al 31 and Bertoglio 32…”
Section: Discussionsupporting
confidence: 93%
“…Our result is consistent with previous studies. 18,31,32 This result could be beneficial to both patients and the health care system. For patients, monthly visit of ports flushing is inconvenient, time-consuming, and expensive, especially when they have completed chemotherapy treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, a meta-analysis showed that a port flushing interval longer than 4 weeks is safe and that extending the flushing interval to 8 weeks might not increase the incidence of total complications and catheter occlusions [ 21 ], which is partly consistent with our study. Fortunately, our research also revealed the safety of exceeding the 4-week flushing interval.…”
Section: Discussionsupporting
confidence: 91%
“…The recent meta-analysis on the prolonged flushing time of totally implantable vascular accesses (TIVAD) by Wu et al published in a recent issue of JVA 1 offers an interesting point of discussion with important clinical implications regarding the management of TIVADs. The flushing modalities of these devices, performed to maintain longterm catheter patency and their correct functioning is still a controversial aspect of maintenance and nursing procedures, are still controversial.…”
mentioning
confidence: 99%